THE RELATIONSHIP BETWEEN SCHOOL PRINCIPALS’ TRANSFORMATIONAL LEADERSHIP AND TEACHERS’ WORK PRODUCTIVITY AT PUBLIC JUNIOR HIGH SCHOOLS IN PADANG UTARA DISTRICT - Andriani, Silvia; Nellitawati, Nellitawati; Jasrial, Jasrial; Luthfiani, Luthfiani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
a